THE PROBLEMATICS OF THE ISLAMIC POLITICAL ARAB IDENTITY: THE ABSENCE OF UMMAH IN THE FICTION OF MUNIS ARAZZAZ - Alkouri, Ahmad Mohd; M.M., Raihanah; Hashim, Ruzy Suliza (Advances in Social Sciences Research Journal, 2015)
This paper explores the problematic of Arab identity based on the absence of the notion of Ummah as represented in the fiction of Jordanian writer Munis Arazzaz. An analytical exploration of the novels of Munis Arazzaz namely, Alive In The Dead Sea (1982), Confessions Of Silencer (1986) and The Maze Of Bedouins In The Mirage Scrappers (1986) focuses on the protagonists’ struggle to reunite the Arabs through a shared sense of national identity. The collective personal journey of the three protagonists, as this paper demonstrates, also parallels the journey of the Arab nation as it struggles to accomplish the mission of Arab unity. Arazzaz, as we problematise, depicts the tension between the Arab nation and the political leaders as a conflict between religious and political attachments. Collectively, the narratives illustrate two significant observations, which appear to foreshadow the current crisis in the Arab world. The first is the Arab nation’s scuffle with its violent autocratic authorities, and the second is the intrusive political strategies used by the State to assert its political identity. These two-pronged conflicts reveal the main argument about the Arab identity crisis today pointing out the absence of the Islamic identity or the sorely missing notion of Ummah. The conclusion drawn from the explication of the narrative indicates that the assertion of political identity contradicts with the propagation of the Ummatic identity. The collective Muslim identity, or the Ummah, appears to be in decline and the crisis continues to linger, causing fragmentation and bitterness as seen in fiction and reality.